Modulating ion channels with nanobodies - Sher Ali; Ashley Suris; Yun Huang; Yubin Zhou (Synthetic and Systems Biotechnology)
Ion channels play instrumental roles in regulating membrane potential and cross-membrane signal transduction, thus making them attractive targets for understanding various physiological processes and associated diseases. Gaining a deeper understanding of their structural and functional properties has significant implications for developing therapeutic interventions. In recent years, nanobodies, single-domain antibody fragments derived from camelids, have emerged as powerful tools in ion channel and synthetic biology research. Their small size, high specificity, and ability to recognize difficult-to-reach epitopes offer advantages over conventional antibodies and biologics. Furthermore, their resemblance to the variable region of human IgG family III reduces immunogenicity concerns. Nanobodies have introduced new opportunities for exploring ion channel structure-function relationships and offer a promising alternative to conventional drugs, which often face challenges such as off-target effects and toxicity. This review highlights recent progress in applying nanobodies to interrogate and modulate ion channel activity, with an emphasis on their potential to overcome current technical and therapeutic limitations.